Beliefs and the Demand for Employee Ownership - Gabriel Burdin; Fabio Landini (Institute of Labor Economics (IZA), 2025)
Why does capital typically hire labor rather than the other way around? Employee-owned firms with majority workforce control—such as worker cooperatives—remain rare in market economies, despite evidence that they perform at least as well as investor-owned firms across various contexts. In this paper, we examine whether beliefs help explain this puzzle by shaping policy preferences and willingness to work in such organizations. In a preregistered experiment guided by a detailed pre-analysis plan, we randomly exposed 2,000 young adults to information from an international expert survey. Respondents held more pessimistic prior beliefs about worker cooperatives compared to experts. Information exposure led to more optimistic beliefs and increased support for pro-cooperative policies. Text analysis of open-ended responses reveals fewer negative and more positive first-order concerns about cooperatives in the treatment group. We also find suggestive evidence of a relative re-ranking of career intentions in favor of worker cooperatives.
Keywords: C91; D83; J24; J54; 330; preferences; employee ownership; cooperatives; information experiment